PERENCANAAN PENDISTRIBUSIAN PRODUK BAHAN BAKAR MINYAK MENGGUNAKAN METODE DISTRIBUTION REQUIREMENT PLANNING (DRP) DI PT. XYZ - Ihda Amalina (2021)
PT. XYZ is a company engaged in oil and gas mining. In this study, the problem that occurs in the company is not in accordance with the number of product requests with products distributed so that it causes the unmet needs of customers. By 2020, unfulfilled products to be distributed reach 70% in a year. For this reason, a well-planned distribution planning is needed using the Distribution Requirement Planning (DRP) method taking into account Lot Sizing and several approaches, including the Economic Order Quantity (EOQ), Period Order Quantity (POQ), and Lot For Lot (LFL) methods to carry out product distribution planning. The products distributed are P1, P2,and P3. Based on the lot sizing method, the method with the most optimal distribution cost is the Lot For Lot (LFL) method for P1 products with a distribution cost of Rp 269,784,000,000 with orders made as many as 103,233,373 liters of products with 48 orders / year, economic order quantity (EOQ) method for P2 products. with a distribution fee of Rp 307,269,806,103 with orders made as much as 193,984,213 liters of products and with 81 orders / year,and the Economic Order Quantity (EOQ) method of P3 products with a distribution fee of Rp 322,974,734,013 with orders made as much as 207,732,568 liters of products with 80 orders/year.